Implementation of Culturally Responsive Teaching in Informatics Learning for Grade VII and VIII Students at UPT SMP Negeri 1 BPR Ranau Tengah - Ismal Ismal; Supandi Supandi; Andi Priyolistiyanto; Wijayanto Wijayanto (Universitas Muhammadiyah Enrekang, 2025)
This study aims to analyze the application of the Culturally Responsive Teaching (CRT) approach in Informatics learning for seventh and eighth grade students at the UPT SMP Negeri 1 BPR Ranau Tengah. CRT is a pedagogical approach that considers students' cultural backgrounds as an important factor in the learning process. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results show that the application of CRT can increase student engagement, strengthen cultural identity, and encourage improved learning outcomes. Teachers integrate local culture into learning projects, utilize community-based technology, and implement differentiated approaches based on student backgrounds. This approach creates a more inclusive and participatory classroom environment; previously passive students become more confident because the material feels relevant to their lives. Teachers also become more responsive to students' diverse needs and potential, enabling them to design adaptive and contextual learning activities. Informatics learning serves not only as a means of transferring technological knowledge but also as a platform for building cultural awareness, collaborative skills, and critical thinking skills. These findings underscore the importance of integrating local values and cultural wisdom in 21st-century learning. Therefore, support from school principals, communities, and educational stakeholders is needed for the sustainable development of culture-based learning practices.